Vicia brulloi (Fabaceae), a new species from Sicily - Sciandrello, Saverio; Galdo, Gianpietro Giusso Del; Salmeri, Cristina; Minissale, Pietro (Phytotaxa, 2019)
Vicia brulloi, a new species from Peloritani range in NE Sicily, is described and illustrated. It is a perennial climbing liane linked to riparian woods, showing close relationship mainly with V. pisiformis, having a scattered European distribution. In particular, V. brulloi is a very rare and extremely localized species morphologically well distinct from V. pisiformis in several remarkable features, such as the dense indumentum covering the vegetative structures and calyces, the shape and size of flower pieces, pods, seeds, as well as seed testa micromorphology. Another relevant peculiarity of V. brulloi is the lower tooth of the calyx replaced by a green leafy appendix, character infrequent in legumes and hitherto never observed in other Vicia species, which clearly represents the residue of its ancestral foliar origin. The morphology, pollen grain and seed testa micromorphology, chromosome complement 2n = 2x = 12, seedling features, reproductive biology, biogeography, habitat, ecology, conservation status and taxonomic relationships of the new species are examined.